(3GdehdO GdfHhjs - (3eLghds ((3eMeO GdNhGes)
(3ChdgG (B:s
(3GdMeO ddg GdPj Ndb hMce hCXgQ HbOQJg GdMce hNW HGdbde aj dhM Ydeg JbOjeG UhQ haQb hQJb haJb hCfYe hQRb hbSe LRjd QRbg JbSjeG chf GdCchGf hdhf GdCdhGf hYde GdEfSGf eG de jYde hcGf aVdg Ydjg YXjeGs
(3BNQgG (B:s
(3GZaQ dfG hGQMefG hdYHjOc GdabQGA hGdOfjG hdLejY GdeSdejf hGdeSdeGJ hGdeDefjf hGdeDefGJ hdCeI eMeO Udi Gddg Ydjg hSde CLeYjf SHMGf QHc QH GdYRI YeG jUahf hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejfs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3aj b(B4(3C Jedc HGSe GdMGL eMeO Hf GdMGL jhSas
Keywords: (3GdJGQjNs